Diseño y construcción de un Banco para ensayos de torsión. - Castillo Cuenca, Ángel Vinicio (2011)
The present Project of Thesis, has the purpose of to DESIGN AND to BUILD A BANK FOR TORSION TEST, same that will contribute in the formation theoretical practice of the students of the Energy,Industries and the Renewable Natural Resources Area of the University National of Loja. The Machine exposed in this project, consists of three fundamental parts: The structural part, the mensuration part and data acquisition. These sections have been properly designed, calculated and selected according to the outlined requirements and to the information gathered for the execution of the project.